1993
DOI: 10.1128/jcm.31.3.665-670.1993
|View full text |Cite
|
Sign up to set email alerts
|

Simple colorimetric microtiter plate hybridization assay for detection of amplified Mycobacterium leprae DNA

Abstract: The detection of amplified products resulting from polymerase chain reactions (PCRs) remains a complicated process. To simplify the detection procedures, we developed a colorimetric microtiter plate hybridization assay for the specific detection of 5'-biotinylated PCR fragments of Mycobacterium leprae DNA. For this assay, an M. leprae DNA capture probe was made and immobilized on the wells of a microtiter plate. Hybridization of the biotin-labeled PCR fragments was detected through enzymatic color development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Existing combinations of PCR and amplicon detection assays will be called 'conventional PCR' throughout this review. The detection components include agarose gel electrophoresis [19], Southern blot [20] and ELISA-like systems [21]. Conventional PCR has been used to obtain quantitative data, with promising results [22].…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Existing combinations of PCR and amplicon detection assays will be called 'conventional PCR' throughout this review. The detection components include agarose gel electrophoresis [19], Southern blot [20] and ELISA-like systems [21]. Conventional PCR has been used to obtain quantitative data, with promising results [22].…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…An objective quantitation of the amplified products would make it possible to determine a significant level of amplified DNA which is clearly relevant for active tuberculosis. Recently, it was shown that the PCR in combination with the colorimetric microwell plate hybridization assay (CoMPHA) could be used for semiquantitative analysis of the level of Mycobacterium leprae template DNA in biopsy specimens (14). Here, we show that 5Ј-biotinylated PCR products of M. tuberculosis can be detected by an M. tuberculosis capture probe in the CoMPHA, allowing a clear distinction between PCR-positive and PCRnegative samples.…”
mentioning
confidence: 83%
“…Amplification with this primer set resulted in a 188-bp fragment with restriction sites at both ends. This fragment was digested and cloned into M13BM20 and subsequently transfected in Escherichia coli as described previously (14). Single-stranded DNA was isolated from the recombinant M13 phages and served as a capture probe for identification of the M. tuberculosis PCR products.…”
mentioning
confidence: 99%
“…Whilst Southern blot detection of amplicon by hybridisation with a labelled oligonucleotide probe (oligoprobe) increases the specificity of amplicon detection, it is time consuming, frequently uses radioactive labels and requires multiple PCR product handling steps, increasing the risk of spreading amplicon throughout the laboratory (Holland et al, 1991). Alternatively, PCR -ELISA has been used to capture amplicon onto a solid phase via biotin or digoxigenin-labelled primers, oligoprobes or by direct capture after incorporation of the biotin or digoxigenin into the amplicon (van der Vliet et al, 1993;Keller et al, 1990;Kemp et al, 1990;Kox et al, 1996;Dekonenko et al, 1997;Watzinger et al, 2001). Once captured, amplicon is detected using an enzyme-labelled avidin or anti-digoxigenin reporter molecule in a manner similar to a standard ELISA format.…”
Section: Real-time Fluorescent Pcr Techniques To Studymentioning
confidence: 99%